Changes in lipidomic profile of aqueous humour in Fuchs endothelial dystrophy - Cabrerizo, Javier; Urcola, Javier Aritz; Vecino, Elena; Melles, Gerrit (Acta ophthalmologica (Oxford, England), 2017)
Purpose To identify and determine differences in lipid profile of aqueous humour (AH) in patients with Fuchs endothelial corneal dystrophy (FECD). Methods Lipidomic profile of eight AH samples of FECD patients and 10 control samples was analysed. Patients with previous history of anterior segment surgery, anterior segment pathology or intraocular injections were excluded. Topical ocular medications within the last 6 months were reported. Aqueous humour (AH) was obtained during the first step of Descemet membrane endothelial keratoplasty in FECD patients and during refractive lensectomy in the control group. Lipidomic ultra‐performance liquid chromatography mass spectrometry was used to perform an optimal profiling of glycerolipids, sterol lipids, sphingolipids and glycerophospholipids. Metabolite extraction was accomplished by fractionating the samples into pools of species with similar physicochemical properties. Results The levels of 27 of 110 lipids change significantly in the AH of FECD eyes when compared to control samples. The concentration of most diacylglycerophosphocholines and 1‐ether, 2‐acylglycerophosphocholines increases in the AH of FECD eyes when compared to healthy controls. In addition, eight sphingomyelins and up to two long‐chain highly unsaturated cholesteryl esters present higher levels in FECD samples when compared to controls. Conclusion The lipid composition of AH in FECD patients differs from that of healthy subjects. Those changes may reflect oxidative stress‐related changes in the lipid metabolism of the corneal endothelial cells in FECD.